CODE SWITHING IN EFL CLASSROOM (A CASE STUDY AT A STATE SENIOR HIGH SCHOOL IN KUPANG) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2018)
This paper is dealing with the issue of code-switching in English classrooms and to investigate when and why teachers in ELT class code-switch when teaching English as a foreign language. Beside observing  teaching and learning process in classroom, two EFL teachers were interviewed and responded to questionnaire. The results showed, as observed, code-switching occurred during the whole process of class by both teacher and students. Based on the interview and respond to the questionnaire, teachers generally tried to code-switch as little as possible but that they did code-switch in some of those situations where the students preferred either a combination of Bahasa Indonesia and English. Teachers’ perception on the students language competence influence the strategy used in teaching English to the class. The teachers code-switched during the class process for different purposes and they all believed that it was an effective tool to enhance learning when employed carefully. Keywords: code-switching; English as a foreign language; classroom